2006
DOI: 10.1016/j.enbuild.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Adding advanced behavioural models in whole building energy simulation: A study on the total energy impact of manual and automated lighting control

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(117 citation statements)
references
References 7 publications
(10 reference statements)
0
101
0
4
Order By: Relevance
“…Thus there is an argument for an automated electricity management strategy which maintains efficient electricity consumption to satisfactorily meet electricity users' electricity needs and meanwhile minimizes the cost of electricity without any user intervention in office buildings. Bourgeois et al [18] show that under automated lighting management the electricity consumption is much less than that in automated lighting management. In the School of Computer Science, there seems to be a debate between the automated strategy and staff-controlled strategy.…”
Section: Experiments 2: Automated Strategy Vs Staff-controlled Strategymentioning
confidence: 99%
“…Thus there is an argument for an automated electricity management strategy which maintains efficient electricity consumption to satisfactorily meet electricity users' electricity needs and meanwhile minimizes the cost of electricity without any user intervention in office buildings. Bourgeois et al [18] show that under automated lighting management the electricity consumption is much less than that in automated lighting management. In the School of Computer Science, there seems to be a debate between the automated strategy and staff-controlled strategy.…”
Section: Experiments 2: Automated Strategy Vs Staff-controlled Strategymentioning
confidence: 99%
“…In this context, user behaviour may be defined as the presence of people in a workplace location in a building and the action users take (or do not take) to influence their indoor environment (Hoes et al, 2009). Recently models have been developed to describe human behaviour and are included in building performance analyses (Bourgeois, Reinhart, & MacDonald, 2006;Degelman, 1999;Hoes et al, 2009;Mahdavi, Kabir, Lambeva, & Proglhof, 2006;Nicol, 2001;Page et al, 2007;Reinhart, 2004;Rijal et al, 2007;Tabak & de Vries, 2010). However, only a few studies successfully demonstrated energy reduction from occupancy behavioural patterns that had been determined because there was no formal connection to the building energy management systems of these buildings (Dong & Andrews, 2009).…”
Section: Human Behaviourmentioning
confidence: 99%
“…low energy cost actuators were exploited as much as possible. The effect of automated blinds and lighting control on heating and cooling requirements were studied in [5]; the authors investigated the reduction of the annual primary energy usage in building climate control for the case of Rome. In the study of [4], the influence of occupant behavior on energy consumption was investigated in a single room occupied by one person.…”
Section: Literature Reviewmentioning
confidence: 99%